An empirical inquiry into the relationship between corporate governance and human resource management - Hazril Izwar Ibrahim; Abdul Hadi Zulkafli (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - Based on the tenets of the stakeholder theory, the study investigates the influence of corporate governance best practices on "hard" and "soft" human resource management practices in public listed companies in Malaysia. Design/methodology/approach - Data was collected from public listed companies in the consumer product sector via structured questionnaire. Multiple regression analysis is conducted using SPSS to test the hypotheses. Findings - The findings suggest that board of directors' independence significantly predicts training and development practices. It is also evidenced that audit committee's effectiveness is significantly related to team-based work. Research limitations/implications - The study is conducted in a single sector of the economy resulted to a small number of listed companies. Originality/value - The significant relationship between board of directors' independence and training and development; and audit committee effectiveness and team-based work indicate that training and development and team-based work are ingrained in the companies' HRM practices, more acceptable and the least complicated to implement. Indicating that public listed companies are answerable to various stakeholders, thus, making it difficult to introduce and implement certain HRM practices.
Keywords: G34; M50; 330; Corporate Governance; Human Resource Management